Duplex Ultrasound Can Successfully Identify Endoleaks and Renovisceral Stent Patency in Patients Undergoing Complex Endovascular Aneurysm Repair. (April 2021) - George, Justin; Tadros, Rami O.; Rao, Ajit; Png, C. Y. Maximilian; Han, Daniel K.; Ilonzo, Nicole; Faries, Peter L.; McKinsey, James F.
Efficacy of duplex ultrasound (DU) surveillance of complex EVAR such as FEVAR and ChEVAR has not been studied. All patients undergoing FEVAR or ChEVAR at a single multihospital institution were retrospectively reviewed. Postoperative surveillance included DU at 1 month and CTA at 3 months. 82 patients met inclusion criteria including 39 (47.6%) ChEVAR and 43 (52.4%) FEVAR cases. DU identified endoleak with aneurysm sac enlargement in 3 cases requiring reintervention. CTA at 3 months detected 2 new endoleaks without growth and 1 renal artery stent occlusion. Replacement of initial postoperative imaging with DU did not result in any missed endoleaks, deaths, ruptures, or branch occlusions.